The influence of surface run-off to 3d slope stability analysis for rainfall induced landslide - Keling, Noraidah; Yusoff, Izham Mohamad; Lateh, Habibah; Ujang, Uznir (2015)

(untitled)
Expansion of urban and recreational developments in hilly areas has resulted in increasing number of residential, commercial properties and infrastructure that is threatened by landslides. A three dimensional (3D) slope stability analysis has emerged recently due to its capability of capturing complex terrain shape in more realistic manners, rather than two-dimensional (2D) approach. The Hovland method is one of the 3D slope stability analysis widely used due to its simple algorithm and practical engineering application. Previous studies have proposed modifying Hovland’s method and integrating it with Geographic Information System (GIS) software to make it practical to be used in a real environment. However, scarce attention has been paid to improve 3D slope stability analysis and to take into account the influence of rainfall induced landslide. This is due to the dynamic behaviour and complex parameters involved. For regions with tropical climate like Malaysia, the study of rainfall induced landslide is crucial due to the many landslide incidents triggered by heavy rainfall. This paper seeks to address this problem by adding the rainfall factor as input to Hovland 3D slope stability analysis in the form of pore water pressure. Rainfall volume can be transformed into infiltration and surface runoff, such as the Infiltrated Excess Overland Flow (IEOF) and Saturated Excess Overland Flow (SEOF). This study only focuses on SEOF as a dynamic variable by using the Topographic Wetness Index (TWI) and Green-Ampt as input for SEOF equation and SEOF later used in pore water pressure computational replacing static water table level. The result of this research is an improved Hovland 3D slope stability analysis method by integrating SEOF factor in the calculation.